A bridge-rehabilitation strategy based on the analysis of a bridge-inspection data set. Issue 1 (28th January 2020) - Dromey, Liam; Ruane, Kieran; Murphy, John J.; O'Rourke, Brian; Lacey, Seán
Abstract : Bridge-management systems (BMSs) allow bridge owners to assess the condition of their bridge stock. However, not all BMS packages have the capability to formulate network-level bridge-rehabilitation investment strategies. This research has developed a decision-support system for bridge owners in the selection of the best strategy for bridge rehabilitation at the network level. The basis of the research is an available data set of 1367 bridge-inspection records for County Cork, Ireland, that has been prepared to the Eirspan BMS inspection standard. The developed system consists of a project-prioritisation procedure that builds on previous research, a methodology for the calculation of a deterioration rate based on published bridge data and, through the use of efficiency and effectiveness indicators taken from international practice, proposes the concept of system performance in the identification of annual rehabilitation investment requirements to achieve full bridge-stock rehabilitation.